Corn and common bean intercropping-system with double and simple corn rows - Filho, Israel Alexandre Pereira; Oliveira, Antônio Carlos de; Cruz, José Carlos (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to identify sowing systems that allow the best condition of common bean yield in intercropping with maize sowed in double and single lines. The trials were carried out at Embrapa-Centro Nacional de Pesquisa de Milho e Sorgo (CNPMS), Minas Gerais State, Brazil, in 1988/89 and 1989/90. The maize cultivars BR 201, Cargill 606 and CMS 350 were sowed in double rows with 50 cm within the pair of double rows, and 150 cm between the pair of double rows at 40,000 and 60,000 plants per hectare. The check was 100 cm single row with 40,000 plants per hectare. Planting density of common beans was 120,000 plants per hectare, which was constant in the systems. Differences were not observed for maize yield between planting systems. Common bean yield decreased when intercropped with maize Cargill 606 and CMS 350 in double lines. The hybrid Cargill 606 in single line increased the yield of the legume. The cultivar BR 201 was the most efficient for intercropping because of higher grain yield average and also because it allowed good average yields of common beans. The planting systems and the climate exerted influence on the grain yields.